The renaming of Asclepias xysmalobioides with Asclepias montevaga (Apocynaceae, Asclepiadoideae) - Glen, Melissa Frances; Nicholas, Ashley; Bester, Stoffel Petrus; Lamb, Jennifer (Phytotaxa, 2015)
Asclepias xysmalobioides Hilliard & B.L. Burtt (1986: 193) is a later homonym of Asclepias xysmalobioides S. Moore (1912: 342). There are no valid synonyms available, and so we propose the new name Asclepias montevaga M. Glen, Nicholas & Bester here.